2022
DOI: 10.1037/ppm0000290
|View full text |Cite
|
Sign up to set email alerts
|

Is it painful? Playing violent video games affects brain responses to painful pictures: An event-related potential study.

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 46 publications
6
26
8
Order By: Relevance
“…Especially, violent video gaming influences and increases pain threshold and pain tolerance for electric‐, temperature‐, and pressure‐related pain stimuli. VVG showed a significantly higher pain threshold and pain tolerance than NGs, whereas NVVG did not significantly differ from NG and VVG in pain threshold and pain tolerance in line with previous findings (Anderson et al., 2010; Bushman & Anderson, 2009; Carnagey et al., 2007; Miedzobrodzka et al., 2022). However, NVVG mean values for pain threshold and pain tolerance were between the mean values for NG and VVG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Especially, violent video gaming influences and increases pain threshold and pain tolerance for electric‐, temperature‐, and pressure‐related pain stimuli. VVG showed a significantly higher pain threshold and pain tolerance than NGs, whereas NVVG did not significantly differ from NG and VVG in pain threshold and pain tolerance in line with previous findings (Anderson et al., 2010; Bushman & Anderson, 2009; Carnagey et al., 2007; Miedzobrodzka et al., 2022). However, NVVG mean values for pain threshold and pain tolerance were between the mean values for NG and VVG.…”
Section: Discussionsupporting
confidence: 91%
“…Teismann et al (2014) found that participants who played violent video games tolerated pain stimuli longer than participants who played a racing game. Habituation to painful pictures among VVGs was confirmed in a recent experiment via event-related potentials for top-down and bottom-up empathy regarding painrelated brain responses by Miedzobrodzka et al (2022). Neuroimaging experiments have shown that VVG results in lower activation of the left lateral medial frontal lobe, the limbic system, such as anterior and posterior cingulate cortex, amygdala, hippocampus, thalamus, cerebellum, posterior and superior parietal lobe, and the entorhinal cortex compared to non-gamers (NGs) for different tasks such as pain exposure or presentation of pictures with negative emotional content (Montag et al, 2012;Palaus et al, 2017;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 66%
“…Indeed, several studies have suggested that playing violent video games is associated with more aggressive thoughts, feelings (hostile affect), and behaviors (see Anderson & Bushman, 2001; Anderson et al, 2010; Calvert et al, 2017; Greitemeyer & Mügge, 2014; Prescott et al, 2018 for meta-analyses), and higher stress levels (Porter & Goolkasian, 2019), suggesting that gamers of these type of video games have specific characteristics. Mostly based on the General Aggression Model proposed by Anderson and Bushman (2002), several studies have shown a positive relationship between violent video game use and aggression in real-world contexts (Anderson & Carnagey, 2009; Anderson et al, 2008; Gabbiadini & Riva, 2018; Greitemeyer, 2019), and short-term desensitization (Miedzobrodzka et al, 2022). On the other hand, some studies failed to find a significant effect of violent video games on aggressive behaviors (Kühn et al, 2019; McCarthy et al, 2016; Przybylski & Weinstein, 2019), hostile feelings (Valadez & Ferguson, 2012), or desensitization in empathy for pain (Kühn et al, 2018), and other meta-analyses reported small effect sizes but also publication bias (Ferguson et al, 2020; Hilgard et al, 2017).…”
Section: Video Games and Personality: Sensation Seeking And Alexithymiamentioning
confidence: 99%
“…Violent video games often depict the suffering of virtual characters; thus, frequent exposure to such games may affect empathy for pain in players. A recent Event-Related Potential (ERP) study indicated that only 40 min of violent gaming is enough to reduce empathy for pain reactions in young adults’ brains who had no prior experience with playing such games (Miedzobrodzka et al, 2022 ). The study further showed that habitual violent gaming exposure was related to lower empathy for pain responses.…”
mentioning
confidence: 99%
“…It is yet unclear, however, whether similar results might also be found in adolescent boys who are often avid game players (Rideout, 2015 ) and whose empathy for pain skills are still developing (Mella et al, 2012 ). Therefore, by applying a similar within-subjects design as in Miedzobrodzka et al ( 2022 ), we investigated whether habitual as well as short-term exposure to violent video games may decrease empathetic brain responses in adolescent players, indicating desensitization.…”
mentioning
confidence: 99%